Chronic Kidney Disease - Chen, Jacqueline; Patel, Ria (The Meducator, 2024)
Chronic kidney disease (CKD) is defined as low filtration function in the kidneys, protein in the urine, or functionally-important structural abnormalities. Low filtration function is associated with waste build-up in the bloodstream and difficulty in excreting salt and water, leading to fluid build-up. CKD may worsen over time, and some individuals with CKD may experience kidney failure, at which point dialysis or transplantation is required to replace kidney function. CKD may be caused by diabetes, renovascular disease, glomerulonephritis, polycystic kidney disease, and various genetic and environmental factors. In 2023, approximately four million Canadians live with and 11-13% of the global population are affected by CKD. This disorder has a 50% five-year mortality rate and is associated with lower quality of life compared to other chronic diseases, including sickle cell anemia, cancer, and cystic fibrosis. CKD’s comorbidities, such as diabetes, are increasing in prevalence and can increase the risk of developing CKD. Thus, the rates of CKD are also set to rise.3 Annual CKD management costs across Canada total $40 billion, with dialysis treatment for people with end-stage kidney disease (ESKD) costing $100,000 per patient.